Pollen Viability and Microspore Culture in Three Broccoli Cultivars (Brassica oleracea L. var. italica Plenck) - Septarini Dian Anitasari; Ida Ayu Astarini; Made Ria Defiani; Made Pharmawati .; Dian Catur Prayantini (Biota, 2019)
Broccoli is a high value vegetable crop in Indonesia, however production is low due to limited number of suitable cultivars, so, breeding hybrid broccoli for warm climate is important. The first step in hybridization is providing homozygote parent plants which can be done efficiently via microspore culture. The objectives of this study were to determine 1) bud size that produce uninucleate microspore stage appropriate for culture; 2) pollen viability, 3) microspore development, in three broccoli cultivars (‘BL 10001’, ‘Royal Green’ and ‘Green Magic’). Various bud size (1 – 5 cm) was squashed and observed microscopically to determine bud size containing uninucleate microspore. Pollen viability was determined by IKI staining and pollen germination method. Chromosome number was counted on root tips using squash method with aceto-orcein stain. Various heat treatment schemes were conducted to induce microspreo development. Result showed uninucleate microspore derived from 2-3 mm and 3-4 mm bud length of ‘BL-10001’ and ‘Royal Green’ was responsive for microspore development in culture. Pollen viability varied among cultivars, 78-87% on IKI method and 15-16% on germination test. Microspore culture showed different embryogenesis response; pollen-like structure was produced by ‘BL 10001’.